Type 2 diabetes and cancer: A retrospective longitudinal comparative cohort study of disease sequence and comorbidity profiles - Maha Alriyami; Amal Saki Malehi; Asil Al Kamyani; Fatema Al Jabri; Maha Alhosni; Khalid Al Saadi; Salim Al-Maqbali; Tahani K. Al-Shuaili; Abdullah Al-Futaisi (PLoS ONE, 2026)
Type 2 Diabetes Mellitus (T2DM) and cancer are major non-communicable diseases that impose a substantial dual burden when they co-occur. However, this dual burden remains understudied and the majority of existing studies investigate T2DM as a comorbidity without distinguishing whether it is pre-existing at the time of cancer diagnosis or newly-onset following diagnosis. This study aimed to investigate the co-occurrence of T2DM and cancer and to assess differences in laboratory variables, comorbidities, complications and overall survival according to the sequence of diagnosis. This retrospective cohort study with longitudinal follow-up included patients diagnosed with both T2DM and cancer. A total of 213 adult patients who meet the inclusion criteria were categorized based on the sequence of diagnosis: T2DM prior to cancer (n = 131) or cancer prior to T2DM (n = 82). The prevalence of T2DM among in-patients with cancer was 27.4%. Statistical analyses were performed to compare clinical and laboratory characteristics between groups. Breast cancer and colon cancers were the most common cancer types. Most patients were diagnosed with T2DM prior to cancer onset and were significantly older than those diagnosed with cancer first ( p = 0.02). Male patients had a higher risk of mortality compared to females (HR = 1.96, p = 0.03). Among patients diagnosed with cancer prior to T2DM, males had significantly higher diastolic blood pressure ( p = 0.02), while females had significantly higher total cholesterol levels ( p = 0.04). No significant differences were observed in comorbidities or complications between groups (all p > 0.05). There were no significant differences in overall survival between the two diagnostic-order groups ( p = 0.03). Moreover, separate survival analysis for breast, colon, lung and gastric cancers showed no significant differences between patients diagnosed with T2DM before cancer and those diagnosed with cancer before T2DM (all p > 0.05). Future studies are warranted to confirm these findings and to better understand the burden of the co-occurrences of T2DM and cancer at national level.